2014
DOI: 10.1002/ajmg.a.36423
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of FMR1 gene mutation and CGG repeat polymorphism in intellectually disabled children in Pakistan

Abstract: Fragile X syndrome is considered the most common heritable form of X-linked intellectual disability (ID). The syndrome is caused by silencing of the fragile X mental retardation 1 gene (Xq27.3) due to hypermethylation. This mutation results in absence or deficit of its protein product, the fragile X mental retardation protein (FMRP) that affects synaptic plasticity in neurons, hence leads to brain dysfunction. The syndrome is widely distributed throughout the world. This study reported for the first time the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The frequency of fragile X-positive patients (5.7%) found in this study is consistent with the literature data reported for individuals with ID/developmental delay (2-9%). 3,[9][10][11] Similar results are observed by L. Angelova 12 among Bulgarian school-age patients with ID, but using a cytogenetic screening method. She reported a 5.9% incidence of the syndrome in a screened group of 76 boys and 25 girls.…”
Section: Discussionsupporting
confidence: 80%
“…The frequency of fragile X-positive patients (5.7%) found in this study is consistent with the literature data reported for individuals with ID/developmental delay (2-9%). 3,[9][10][11] Similar results are observed by L. Angelova 12 among Bulgarian school-age patients with ID, but using a cytogenetic screening method. She reported a 5.9% incidence of the syndrome in a screened group of 76 boys and 25 girls.…”
Section: Discussionsupporting
confidence: 80%
“…Small sample size of 850 is also a drawback in comparison to some similar studies reported elsewhere [ 36 ]. Two studies from Asia have reported on small samples of less than 500 [ 48 , 49 ]. However, the fact that no females with FXS were detected in our study may have been due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Also, exclusion of more prevalent conditions for intellectual impairment, such as Down syndrome in the sampling process could be seen as causing a biased over-estimation in the overall prevalence figure. However, similar exclusion criteria have been used in other studies on comparable populations [11,12]. The benefit here is that it allows for the apperception of FXS as a possible cause in those with intellectual impairment of unknown aetiology.…”
Section: Child and The Capillary Electrophoresis And Tested Firstmentioning
confidence: 99%
“…In contrast FXS-PM, prevalence rates are high with 1:130 to 1:256 reported for females, and 1:250 to 1:813 for males [7,8]. The rates are mostly from West European populations, but figures for other ethnically diverse populations are also known [9][10][11][12]. Prevalence rates of South Asian populations are limited.…”
Section: Introductionmentioning
confidence: 98%